Cracking Windows Phone and BlackBerry Native Development Cross-Platform Mobile Apps Without the Kludge - Baxter-Reynolds, Matthew (Apress : Imprint: Apress, 2011)
You've developed a killer app for one mobile device-now it's time to maximize your intellectual investment and develop for the full spectrum of mobile platforms and devices. With Cracking Windows Phone and BlackBerry Native Development, you'll learn how to quickly retool your application between the Windows Phone 7, Windows Mobile, and BlackBerry platforms and broaden the interest and audience of your app. Cracking Windows Phone and BlackBerry Native Development takes you through the same mobile software development project on each platform, learning the differences between and the relative strengths and weaknesses of each platform as you go. No magic intermediate layers of obfuscation-by the time you get to the end, you'll be an expert at developing for any of the major smartphone platforms using each vendor's preferred toolset and approach.  Cracking Windows Phone and BlackBerry Native Development covers the Windows Phone 7, Windows Mobile, and BlackBerry platforms, as well as the development of a general web application accessible on other devices.  If you're interested in taking your app into the world of iPhone and Android, be sure to check out the companion volume, Cracking iPhone and Android Native Development, at http://www.apress.com/9781430231981.